Implementasi Search Engine Optimization untuk Meningkatkan Trafik Website About MYLPGO - Valeri Christian Rudinie; Sudirman; Afifah (KHARISMA Tech, 2022)
Website about MYLPGO is a website that explains the LPGO sales applicationwhich contains information of using it and the benefits that can be obtained from using the LPGO application. This application is already available on Playstore. Since its release, the website has caused problems in terms of visitor traffic where the number that appears is very small and search engines does not appear on the website so a SEO On Page method is needed to overcome these problems. The first step in the process of implementing SEO On Page is to determine keywords and make improvements to the website to add meta titles, descriptions, headings and etc. By implementing the SEO On Page method on the website, it results in a very drastic increase in the number of visitor traffic and displays the search engine on the first page on the website which is carried out using tests on Google Search Console and Google Analytics.